MFI Capital Structure Decision Making : A Call for Greater Awareness - Deshpande, Rani; Nestor, Camilla; Abrams, Julie (World Bank, Washington, DC, 2012)
Microfinance institutions (MFIs) today have an increasingly broad range of financing sources at their disposal. This allows for greater funding diversification, but it also makes decisions about capital structure more complex. Several high-profile financing transactions for MFIs have taken place recently, including securitizations, local bond issues, the first large-scale venture capital investment in an MFI, and the first Initial Public Offering of shares. In addition, where their legal structure permits, many MFIs are launching large-scale deposit mobilization campaigns as a core funding strategy. Consultative Group to Assist the Poor (CGAP) and Grameen Foundation recently conducted a survey of MFI managers to better understand MFI capital structure decision-making processes in the face of these expanding financing options.